A new case of GABA transaminase deficiency facilitated by proton MR spectroscopy - Tsuji, Megumi (Springer Netherlands, 2010)
BACKGROUND: Deficiency of 4-aminobutyrate aminotransferase (GABA-T) is a rare disorder of GABA catabolism, with only a single sibship reported. We report on a third case, a Japanese female infant with severe psychomotor retardation and recurrent episodic lethargy with intractable seizures, with the diagnosis facilitated by proton magnetic resonance (MR) spectroscopy ((1)H-MRS). METHODS: Neuroimaging was performed at the first episode of lethargy. For (1)H-MRS, locations were placed in the semioval center and the basal ganglia. Quantification of metabolite concentrations were derived using the LCModel. We confirmed the diagnosis subsequently by enzyme and molecular studies, which involved direct DNA sequence analysis and the development of a novel multiplex ligation-dependent probe amplification test. RESULTS: (1)H-MRS analysis revealed an elevated GABA concentration in the basal ganglia (2.9 mmol/l). Based on the results of quantitative (1)H-MRS and clinical findings, GABA-T deficiency was suspected and confirmed in cultured lymphoblasts. Molecular studies of the GABA-T gene revealed compound heterozygosity for a deletion of one exon and a missense mutation, 275G>A, which was not detected in 210 control chromosomes. CONCLUSIONS: Our results suggest that excessive prenatal GABA exposure in the central nervous system (CNS) was responsible for the clinical manifestations of GABA transaminase deficiency. Our findings suggest the dual nature of GABA as an excitatory molecule early in life, followed by a functional switch to an inhibitory species later in development. Furthermore, quantitative (1)H-MRS appears to be a useful, noninvasive tool for detecting inborn errors of GABA metabolism in the CNS.